2014
DOI: 10.1002/hed.23477
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes among patients with head and neck cancer treated by intensity‐modulated radiotherapy with and without adaptive replanning

Abstract: Although the use of routine replanning is probably not necessary, our findings do suggest a significant benefit in appropriately selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
134
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(145 citation statements)
references
References 17 publications
10
134
1
Order By: Relevance
“…For IMRT treatment, up to two adaptation steps was reported to be sufficient and is logistically feasible 13, 14, 15, 16. Adaptive IMRT has been shown to be associated with improved locoregional control,17 especially for advanced tumor stages 18…”
Section: Introductionmentioning
confidence: 99%
“…For IMRT treatment, up to two adaptation steps was reported to be sufficient and is logistically feasible 13, 14, 15, 16. Adaptive IMRT has been shown to be associated with improved locoregional control,17 especially for advanced tumor stages 18…”
Section: Introductionmentioning
confidence: 99%
“…However, the researchers admitted that the residual setup error was still largely responsible for causing the dosimetric deviation that occurred after CBCT image guidance was used to correct the translational setup. Additionally, when researching the effect of adaptive replanning on locoregional control, Zhao et al [22] and Chen et al [23] argued that routine replanning was probably not necessary but still suggested that there would be a significant benefit if appropriate patients were selected.…”
Section: Discussionmentioning
confidence: 99%
“…The timing of replanning is a controversial topic in parotid protection-based ART in head and neck cancer. Someone recommended replanning when it became obvious that a tumor had shrunk, weight loss had occurred, or skin separation had reduced [7,11,12,[21][22][23], while others believe that replanning should be performed when a specific fraction has been reached [26][27][28]. Our precious study found that parotid volume variation presented a linear pattern throughout IMRT of NPC realized by HT technique, and the rate of volume variation reached its peak at the 16th fraction and then decreased gradually, suggesting that replanning is appropriate in the fourth week [14].…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10] Interfractional anatomical changes, in turn, can substantially alter dose deposition, suggesting a benefit to adaptive replanning. [7][8][9][10][11][12][13][14][15][16][17][18][19] However, adaptive replanning remains to be widely adopted owing to its time-intensive nature and an unclear threshold of anatomical changes required for its posited benefit. 10,11,16,20 The aforementioned studies of anatomical alteration during IMRT relied on CT imaging, which might not provide optimal soft-tissue contrast/ resolution, leading to possible interobserver variability.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16][17][18][19] However, adaptive replanning remains to be widely adopted owing to its time-intensive nature and an unclear threshold of anatomical changes required for its posited benefit. 10,11,16,20 The aforementioned studies of anatomical alteration during IMRT relied on CT imaging, which might not provide optimal soft-tissue contrast/ resolution, leading to possible interobserver variability. 21,22 MRI provides superior soft-tissue resolution, 2,21,23,24 potentially allowing for a more accurate evaluation of anatomical changes during IMRT.…”
Section: Introductionmentioning
confidence: 99%